If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -3 + 3x = -53 Reorder the terms: -3 + 7x + 3x = -53 Combine like terms: 7x + 3x = 10x -3 + 10x = -53 Solving -3 + 10x = -53 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 10x = -53 + 3 Combine like terms: -3 + 3 = 0 0 + 10x = -53 + 3 10x = -53 + 3 Combine like terms: -53 + 3 = -50 10x = -50 Divide each side by '10'. x = -5 Simplifying x = -5
| -7+2(3+p)=23+6p | | 1/3x+5=1 | | 3(x-2)+12(x+1)=-24 | | 2thirdsx-7=11 | | 5-5y=-35 | | (-8)+(3*4)-x=0 | | -7(2-8v)=-14+12v | | 5=-4x+7x+5 | | 4+x-3=2x+1-x | | x+35+4x= | | -16-8x=4(-5x+5) | | x+(0.18x)=7503 | | 10-7n=-6(2n+5) | | 2x^2+6x-602=0 | | p+21=3(p+7) | | 5x-18=90-4x | | 3x+7+8x+8=26 | | 2x-17=-15 | | (x-6)^2/3-5=0 | | (9/16)x=4/3 | | 15=3x+x+3 | | (28x-1)-9(3x+2)=-7 | | -1+2x+7x=-1 | | 2=6x+3x+2 | | (6g^3+7h)+-8g^3= | | 7x-20=-x+2(x+5) | | -1/3y-2/5=-1/4 | | 2x^2+3k-8=0 | | -7x-9-4x=13 | | 6x+5+8x+9=98 | | 7m+4=63 | | 4/10=12/20 |